The Effect of Monitoring and Evaluation on Quality Assurance in Higher Education (A Case Study of Accra Technical University (Atu), Accra-Ghana) - Koomson, Gifty Ahwireng; Danso, Mabel Korankye; Dortey, Esther Ansah (European Journal of Applied Sciences, 2022)
The study aimed to examine the effect of monitoring and evaluation on quality assurance in higher education using Accra Technical University, Accra- Ghana. The study was guided by three research questions grounded in the literature of monitoring and evaluation and quality assurance in higher education. The mixed method research approach which involves both qualitative and quantitative approach was employed for the study. A convenience sampling technique was used to select 60 respondents. Questionnaire and interview were the main data collection instrument. Statistical Product for Service Solution (SPSS) was used in the analysis of the data. Pearson correlation coefficient tool (t-test), chi – square, frequencies, percentages and tables were used to present the data. The study revealed that distractions by colleagues, conflict of interests by superior officers, insufficient financial resources, lack of support from management and difficulties in accessing information are some of the challenges to effective monitoring and evaluation in higher education. It was also discovered that monitoring and evaluation helps to deliver good quality assurance results in terms of – content, professional development, leadership, academic results. It was recommended that there should be continued managerial support through resource allocation to address non-conformities in the quality assurance policies in the university. It was also recommended that there should be extensive examination of the nature of relationship that exists between the vice chancellor registrar, examination department and the quality assurance directorate in the university by focusing on the exact landscape of the relationship as this will help to understand the strengths and drawbacks of the existing relationship.